Предмет: Алгебра,
автор: rota99
все корни уравнения 3x^2-5x/6=x+1/9
Приложения:
Ответы
Автор ответа:
0
Решение:
3x^2-5x/6=x+1/9 приведём к общему знаменателю 18
54x^2-15x-18x-2=0
54x^2-33x-2=0
x1,2=[33+-sqrt{1089-4*54*(-2)}]/54*2=[33+-sqrt(1089+432)]/108=(33+-sqrt1521)/108=
=(33+-39)/108
x1=(33+39)/108=72/108=2/3
x2=33-39=-6/108=-1/18
Ответ: х1=2/3 х2=-1/18
3x^2-5x/6=x+1/9 приведём к общему знаменателю 18
54x^2-15x-18x-2=0
54x^2-33x-2=0
x1,2=[33+-sqrt{1089-4*54*(-2)}]/54*2=[33+-sqrt(1089+432)]/108=(33+-sqrt1521)/108=
=(33+-39)/108
x1=(33+39)/108=72/108=2/3
x2=33-39=-6/108=-1/18
Ответ: х1=2/3 х2=-1/18
Автор ответа:
0
спасибо 5получил
Похожие вопросы
Предмет: Математика,
автор: dndndnva017
Предмет: Информатика,
автор: 0811tolik0811
Предмет: Математика,
автор: SofiaHaritonova15
Предмет: Информатика,
автор: 23bdfud